An RDF based approach for integrating data at different levels of abstraction - Avelino, Jones de Oliveira; Cordeiro, Kelli de Faria; Cavalcanti, Maria Cláudia (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
The growth and diversity of data sources have been a challenge for data interoperability. Although there are several initiatives to face this challenge, there are still difficulties especially when data are at different levels of abstraction. In this sense, this article proposes INTEGRA, an RDF-based approach, which takes advantage of the graph flexibility. It allows the integration of heterogeneous data sources through interconnections between schemas, between instances, and between instance-schema. Additionally, we present a case study in the Software Development Management scenario, which shows INTEGRA feasibility and its benefits.